Réponses

  • Utilisateur Brainly
2014-04-27T18:25:37+02:00
A(2;0) ; B(-√2;√2) ; I(1-√2/2;√2/2) ; O(0;0)
OI²=(1-√2/2)²+(√2/2)²=1+1/2-√2+1/2=2-√2
donc OI=√(2-√2)

l'angle (i,OI) mesure 1/2*(i,OB) car OAB est isocèle en O
donc (i,OI)=1/2*3π/4=3π/8 rad

par définition du cercle trigonométrique :
I(r*cos(3π/8);r*sin(3π/8))
donc I(√(2-√2))*cos(3π/8);√(2-√2))*sin(3π/8))

alors √(2-√2)*cos(3π/8)=1-√2/2
donc cos(3π/8)=(1-√2/2)/√(2-√2))=1/2*(2-√2)/√(2-√2)=1/2*√(2-√2)=√(2-√2))/2
de même on obtient sin(3π/8)=√(2+√2)/2